O ensino de crianças com transtorno do espectro autista numa escola do campo no município de Abaetetuba/PA - SILVA, Thamyres Silva da (2023)
This work deals with the pedagogical practices of teachers with children with autism spectrum disorder (ASD) at the Cristo Salvador School located in the rural area of the municipality of Abaetetuba/PA. Its research problem is to understand how a rural school works with children on the autistic spectrum. The objective of this work is to describe the pedagogical practices that the main teachers and school support professionals (SAP) use to work with children with autism spectrum disorder. The research is of a qualitative nature, being used as a tool for data collection, semi-structured interviews, photos, observations and notes. As a theoretical support, we used Paulo Liberalesso (2020), Lucelmo Lacerda (2020), Mayra Gaiato (2018), Gustavo Teixeira (2018) who deal with the perspective of inclusion of students with ASD. The results indicate that the school does not have an adequate physical structure, lack of a recreational room. On the other hand, the teachers produce the adapted didactic material and carry out their pedagogical practices in reading both in the classroom and in the external environment. The school's management promotes moments of lectures and films with teachers and students focusing on the discussion on inclusion.